Educação física, pedagogia decolonial e saberes indígenas : experiências docentes em escolas estaduais de Barra do Garças/MT - Silva, Lais Cristina Barbosa (2024)
The present study materializes from concerns about the relationships between body, difference, and physical education, focusing on the ethnic-racial relations that emerge in the school context. The general objective of the research was to investigate teaching experiences regarding indigenous knowledge in Physical Education classes, with the aim of recognizing how differences permeate state public schools in Barra do Garças (MT). Specifically, the research sought to: a) study how indigenous knowledge emerges in Brazilian Physical Education, from the perspective of decolonial pedagogy; b) identify teaching experiences related to indigenous knowledge in Physical Education classes manifested in the daily school life of Barra do Garças (MT); and c) recognize how ethnic-racial differences, based on indigenous knowledge, can provide elements for the production of a decolonial Physical Education. Methodologically, the research was carried out in four stages, namely: I) initial contact with the State Department of Education of Mato Grosso (SEDUC), for authorization from the responsible body for the research; II) mapping of state schools in the city, where it is possible to identify the enrollment of indigenous students in high school; III) contact with Physical Education teachers from the state school system, whose classes have indigenous students, with acceptance for the realization of semi-structured interviews; and IV) transcription process, analysis – following Content Analysis guidelines – and interpretation of data, based on literature dealing with Decolonial Education and beyond. As a result of the research, it is evident that teachers are aware of the need to address Indigenous Knowledge, recognizing its importance and proposing changes for a Decolonial Physical Education. They also advocate for the inclusion of these knowledges in the initial training of teachers, while acknowledging practical challenges, especially the lack of knowledge about indigenous culture. In ongoing school training, the systematic absence of these knowledges hampers their inclusion in classes, emphasizing the importance of the Regional Directorate of Education (DRE) in promoting the inclusion of indigenous culture in Physical Education, as well as regional discussions on cultural diversity, political actions, and alliances to address the unjust reality. Despite being familiar with documents contributing to pedagogical implementation, teachers do not know how to address Indigenous Knowledge, citing cultural communication, i.e., the indigenous mother tongue, as the main challenge, hindering dialogue. Although some teachers report addressing these knowledges, they could not describe how this integration occurs. Residual traces of colonialism in Physical Education are emphasized, demanding overcoming and intervention based on Law 11.645, which addresses the teaching of indigenous history and culture, aiming to deconstruct power relations present in 'other' cultures. In summary, the study suggests Interculturality and Decolonial Pedagogy as proposals to promote insurgencies, resistance, and transgression of dominant pedagogical practices.